2021
DOI: 10.3389/fonc.2021.614052
|View full text |Cite
|
Sign up to set email alerts
|

MRI Radiomics Signature as a Potential Biomarker for Predicting KRAS Status in Locally Advanced Rectal Cancer Patients

Abstract: Background and PurposeLocally advanced rectal cancer (LARC) is a heterogeneous disease with little information about KRAS status and image features. The purpose of this study was to analyze the association between T2 magnetic resonance imaging (MRI) radiomics features and KRAS status in LARC patients.Material and MethodsEighty-three patients with KRAS status information and T2 MRI images between 2012.05 and 2019.09 were included. Least absolute shrinkage and selection operator (LASSO) regression was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Beyond the morphological information of rectal cancer, more mineable data within the medical images have been extracted using machine learning such as radiomics and DL, which could reflect tumor heterogeneity 38–40 . Prior MRI‐based radiomics models reported by Meng et al and Zhang et al achieved moderate performance in evaluating KRAS status in rectal cancer with AUCs of 0.651 and 0.703 39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the morphological information of rectal cancer, more mineable data within the medical images have been extracted using machine learning such as radiomics and DL, which could reflect tumor heterogeneity 38–40 . Prior MRI‐based radiomics models reported by Meng et al and Zhang et al achieved moderate performance in evaluating KRAS status in rectal cancer with AUCs of 0.651 and 0.703 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the morphological information of rectal cancer, more mineable data within the medical images have been extracted using machine learning such as radiomics and DL, which could reflect tumor heterogeneity. [38][39][40] Prior MRIbased radiomics models reported by Meng et al and Zhang et al achieved moderate performance in evaluating KRAS status in rectal cancer with AUCs of 0.651 and 0.703. 39,40 Similar results were found in our prior study focusing on the value of MRI-based hand-crafted radiomics in identifying KRAS mutation in rectal cancer, moderate performance with AUCs of 0.682 and 0.714 were observed in the internal and external validation datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, one radiomic feature named X. LL_scaled_std was selected. In the validation set, the radiomics‐based C‐index value was 0.703 38 . Furthermore, applying AI to predict genotyping could reduce the cost of testing and the time and expense of treatment 39 …”
Section: Clinical Applications Of Ai In Rc Based On Mrimentioning
confidence: 99%
“…In 2016, the National Comprehensive Cancer Network guidelines recommended that all patients with suspected or confirmed metastatic CRC should be tested for KRAS / NRAS / BRAF mutations, but this requires pathological tissue specimens. It is gratifying that some radiogenomics studies have shown that the radiomic characteristics of CT and MRI may help to predict the genotype of CRC tumors before surgery[ 93 - 95 ]. Yang et al [ 96 ] reported that CT radiomic characteristics were associated with KRAS / NRAS / BRAF mutations.…”
Section: Radiomics Workflowmentioning
confidence: 99%